Traction electric drive for a hybrid shunting locomotive - Kachan, Andrii (National Technical University "Kharkiv Polytechnic Institute", 2024)
The research deals with expanding use of hybrid locomotives for shunting operations and short-distance train work under condition where the rated power of the locomotive is realized within a short period of time. High traction and energy characteristics are provided by a traction electric drive based on AC electric motors. To reduce fuel consumption and NOx emissions on-board energy storage systems are used. For specialized train tasks, battery locomotives are used. Their on-board energy storage system is created based on lithium cells, providing necessary energy reserve for autonomous operation, according to operating conditions.
Keywords: hybrid locomotives; battery locomotives; shunting operations; short-distance train; traction electric drive; on-board energy storage system